2009
DOI: 10.4161/psb.4.10.9709
|View full text |Cite
|
Sign up to set email alerts
|

Sustained growth promotion in Arabidopsis with long-term exposure to the beneficial soil bacteriumBacillus subtilis(GB03)

Abstract: Volatile emissions from the commercial growth promoting soil bacterium Bacillus subtilis (GB03) are effective in augmenting short-term growth, photosynthetic capacity and salt tolerance in Petri-dish grown arabidopsis seedlings. In contrast, the impact sustained GB03 volatile exposure on plant growth and development has yet to be examined. here is provided physical and physiological data establishing that bacterial volatiles induce long-term growth promotion, elevated photosynthetic capacity and iron accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 31 publications
7
70
1
1
Order By: Relevance
“…Recent discoveries have shown that plants also interact with a variety of PGPRs that are capable of increasing photosynthetic capacity (Xie et al 2009;Zhang et al 2008b), conferring drought and salt tolerance (Dimkpa et al 2009;Xie et al 2009;Zhang et al 2008aZhang et al , 2009aZhang et al , 2010, increase disease suppression (Chithrashree et al 2011;Jetiyanon and Kloepper 2002;Okubara and Bonsall 2008), plant growth (Hayat et al 2010;Lim and Kim 2009), and improving the effectiveness of the plant's own iron acquisition mechanisms (Zhang et al 2009a). These discoveries may offer potential for PGPR applications to improve agricultural production and sustainability.…”
Section: Role Of Soil Microbes In Soil Health and Plant Productivitymentioning
confidence: 98%
“…Recent discoveries have shown that plants also interact with a variety of PGPRs that are capable of increasing photosynthetic capacity (Xie et al 2009;Zhang et al 2008b), conferring drought and salt tolerance (Dimkpa et al 2009;Xie et al 2009;Zhang et al 2008aZhang et al , 2009aZhang et al , 2010, increase disease suppression (Chithrashree et al 2011;Jetiyanon and Kloepper 2002;Okubara and Bonsall 2008), plant growth (Hayat et al 2010;Lim and Kim 2009), and improving the effectiveness of the plant's own iron acquisition mechanisms (Zhang et al 2009a). These discoveries may offer potential for PGPR applications to improve agricultural production and sustainability.…”
Section: Role Of Soil Microbes In Soil Health and Plant Productivitymentioning
confidence: 98%
“…With PGPR-induced salt tolerance, the sodium uptake transporter HKT1 has been shown to be organ specifically regulated in Arabidopsis by B. subtilis resulting in reduced endogenous sodium when plants are grown with elevated salt (Zhang et al 2008). For growth promotion, PGPR have been linked with auxin redistribution from leaves to roots that in turn is associated with foliar cell expansion and lateral root proliferation in Arabidopsis (Zhang et al 2007;Xie et al 2009). …”
Section: Introductionmentioning
confidence: 97%
“…With emerging extreme climatic changes, another critical question is whether cropping system sustainability can be increased by using plants that can interact with a variety of PGPR/B that are capable of increasing photosynthetic capacity [126,127], conferring drought and salt tolerance [126,[128][129][130], and improving the effectiveness of the plant's own iron acquisition mechanisms [129]. A variety of companies have begun to offer new products that consist of PGPR/B inoculants (soil and/or seed treatments), or chemicals aimed at increasing root exudation to help foster PGPR/B establishment.…”
Section: Specific Approach: Plant Selection and Microbial Amendmentsmentioning
confidence: 99%